Interview de Prof Franca avec Diallo (Socio-anthropological study on endogenous sources of dialogue and peace against terrorism in Burkina Faso, 2022)
From December 13 to 15, 2021, an international symposium was held in Ouagadougou, Burkina Faso, on the theme: Terrorism in Burkina Faso: to negotiate or not to negotiate.
Keywords: Terrorism; Dialogue; Mediation; Peace